PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBANTU APLIKASI PIXTON PADA MATERI KEARIFAN LOKAL DI KELAS V SEKOLAH DASAR - Desita Nova; Hendra Budiono; Husnul Badri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research and development aims to (1) develop learning media in the form of digital comics assisted by the Pixton application on local wisdom material for fifth-grade elementary school students, (2) determine the validity level of the developed digital comic media, and (3) determine its practicality when implemented in learning. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SD Negeri 3/IV Kota Jambi with fifth-grade students as trial subjects and involved material experts, media experts, and language experts as validators. Data were collected through validation sheets and response questionnaires from teachers and students, then analyzed using qualitative and quantitative techniques. The results showed that the material expert validation obtained an average score of 4.80, categorized as very valid; media expert validation obtained an average score of 4.72, categorized as very valid; and language expert validation obtained an average score of 4.80, categorized as very valid. Teacher response questionnaires yielded an average score of 4.73, while student responses resulted in average scores of 4.85 in the small-group trial and 4.87 in the large-group trial, both categorized as very practical. It can be concluded that the digital comic learning media assisted by Pixton is highly valid and practical to be used as a learning medium for local wisdom material in fifth-grade elementary school.